2018
DOI: 10.1155/2018/4945157
|View full text |Cite
|
Sign up to set email alerts
|

Application and Development of Enhanced Chaotic Grasshopper Optimization Algorithms

Abstract: In recent years, metaheuristic algorithms have revolutionized the world with their better problem solving capacity. Any metaheuristic algorithm has two phases: exploration and exploitation. e ability of the algorithm to solve a difficult optimization problem depends upon the efficacy of these two phases. ese two phases are tied with a bridging mechanism, which plays an important role. is paper presents an application of chaotic maps to improve the bridging mechanism of Grasshopper Optimisation Algorithm (GOA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The effectiveness of NBGOA was evaluated using 20 datasets with various sizes taken from the UCI datasets repository in comparison with five well-regarded optimization techniques in the feature selection field. Simulation results revealed that BGOA [78] NBGOA [79] BGOA [67] ECGOAs [80] LMGOA [81] ECGOA [82] CGOA [83] CGOA [84] SFECGOAs [85] OLCGOA [86] ECGOAs [87] ECAGOA [88] IGOA [70] EGOA [89] PGOA [90] LGOA [91] IGOA [92] AGOA [93] MI-LFGOA [94] LGOA [95] GOA_EPD [65] DJGOA [96] DQBGOA_MR [97] Fuzzy GOA [98] GO-FLC [99] EGOA-FC [100] AGOA [69] AGOA [101] GHO [102] self-adaptive GOA [103] OGOA [104] OBLGOA [105] IGOA [106] MOGOA [75] MOGOA [76] MOGOA [66] MOGOA [107] MOGOA [108] MOGOA [109] LWSGOA [110] MGOA [111] GOFS [112] PCA-GOA [113] OGOA [114] IGOA [115] Fractional-GOA…”
Section: ) Binary Grasshopper Optimization Algorithmmentioning
confidence: 99%
“…The effectiveness of NBGOA was evaluated using 20 datasets with various sizes taken from the UCI datasets repository in comparison with five well-regarded optimization techniques in the feature selection field. Simulation results revealed that BGOA [78] NBGOA [79] BGOA [67] ECGOAs [80] LMGOA [81] ECGOA [82] CGOA [83] CGOA [84] SFECGOAs [85] OLCGOA [86] ECGOAs [87] ECAGOA [88] IGOA [70] EGOA [89] PGOA [90] LGOA [91] IGOA [92] AGOA [93] MI-LFGOA [94] LGOA [95] GOA_EPD [65] DJGOA [96] DQBGOA_MR [97] Fuzzy GOA [98] GO-FLC [99] EGOA-FC [100] AGOA [69] AGOA [101] GHO [102] self-adaptive GOA [103] OGOA [104] OBLGOA [105] IGOA [106] MOGOA [75] MOGOA [76] MOGOA [66] MOGOA [107] MOGOA [108] MOGOA [109] LWSGOA [110] MGOA [111] GOFS [112] PCA-GOA [113] OGOA [114] IGOA [115] Fractional-GOA…”
Section: ) Binary Grasshopper Optimization Algorithmmentioning
confidence: 99%
“…Hence, the value of c decreases with increasing iteration. To improve GOA's accuracy in finding GMPP, Akash Saxena et al [27] added some randomness in GOA. The authors referred to their method as enhanced chaotic GOA (ECGOA).…”
Section: Review Of Grasshopper Optimization Algorithmmentioning
confidence: 99%
“…The authors referred to their method as enhanced chaotic GOA (ECGOA). This random parameter x l is added to c, and, according to [27], the value of x l is within different ranges for the following four cases:…”
Section: Review Of Grasshopper Optimization Algorithmmentioning
confidence: 99%
“…The Enhanced chaotic grasshopper optimization algorithm (ECGOA)are used to find the parameter and it reduces speedily to reach the comfort zone. The different chaotic sequences [28] [29] are used and the chaotic Logistic map is quite exciting to implement for AVR system [3]. The Logistic chaotic map expression is given in Eqn.…”
Section: Grasshopper Optimization Algorithmmentioning
confidence: 99%